A Journey From Sympathy to Empathy - Horne, Samantha (Auckland University of Technology, 2019)
Ava is a happy, healthy child living in a middle-class family in Hawke’s Bay, New Zealand. However, as she grows up, she becomes increasingly aware of her mother’s irrational behaviour that stems from the emotional trauma of tragically losing her first husband and young son. Ava struggles with her emotions and guilt as her dad tries to maintain the peace and keep the family together. An incident just before Ava’s birthday sees her discovering comfort in the rich food at her party, which sets her on a rollercoaster of bingeing, purging, and starvation in a desperate bid to lose weight and feel better about herself. When Ava is diagnosed with diabetes, she discovers a secret world of weight loss that is both blissfully effective and incredibly dangerous as she plays Russian roulette with her life. When Ava’s eating disorder is finally discovered and she is hospitalised, she forms an unlikely bond with a fellow patient. But with the sudden death of this ally, Ava is forced to confront her demons as she realises that there is much at stake, including her own life, if she doesn’t alter her path of self-destruction. With a passion that is fuelled by the needless death of her friend and the strength that she musters from the unconditional love of her husband and daughter, she embarks on the galling journey of recovery. But will Ava truly be able to beat the cancerous effects of her eating disorder, or could its destruction return and spread through the people that she loves the most?
Keywords: Diabulaemia; Eating disorder; Anorexia; Empathy